2009
DOI: 10.1016/j.desal.2008.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Montmorillonite–Cu(II)/Fe(III) oxides magnetic material for removal of cyanobacterial Microcystis aeruginosa and its regeneration

Abstract: In this paper, montmorillonite-Cu(II)/Fe(III) oxides magnetic material was prepared and used for removal of harmful algae from water. The material was prepared by the supporting of Cu(II)/Fe(III) oxides on pillared montmorillonite and was characterized by XRD, zeta potential measurements. The results showed that the whole material is magnetic. The prepared magnetic material was effective for the removal of cyanobacterial Microcystis aeruginosa and the loaded particles was chemically regenerated using acetone s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…However, the common disadvantage of Fe3O4 NPs is its decrease of surface charge at neutral and alkaline pH conditions [18]. Gao et al (2009) developed montmorillonite-Cu(II)/Fe(III) for the harvesting of Microcystis aeruginosa, but the harvesting efficiencies still decreased at high pH values [24]. Ge et al (2015) overcame the limitation of Fe3O4 NPs by coating polyethylenimine (PEI) on the surface of Fe3O4 NPs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the common disadvantage of Fe3O4 NPs is its decrease of surface charge at neutral and alkaline pH conditions [18]. Gao et al (2009) developed montmorillonite-Cu(II)/Fe(III) for the harvesting of Microcystis aeruginosa, but the harvesting efficiencies still decreased at high pH values [24]. Ge et al (2015) overcame the limitation of Fe3O4 NPs by coating polyethylenimine (PEI) on the surface of Fe3O4 NPs.…”
Section: Discussionmentioning
confidence: 99%
“…taste, turbidity and odor. The methods used for algae removal include centrifugation, microstraining, coagulation, in-pond chemical precipitation, filtration, flotation and ion exchange (Bitton et al, 1975;Gao et al, 2009).…”
Section: Removal Of Microalgal Biomassmentioning
confidence: 99%
“…The use of Nano-Fe 3 O 4 has great practical value in other applications (as shown in Table 4). In addition, to the water environment, a number of studies had shown that Nano-Fe 3 O 4 can effectively remove heavy metals from sewage and also remove organic, inorganic compounds, dyes, algae [132] and other environmental pollutants in water. Ito et al [133] studied the effect of ZrFe 2 (OH) 8 as adsorbent on phosphorus removal in wastewater.…”
Section: Othersmentioning
confidence: 99%